Species Diversity and Distribution Patterns of Epiphytic Orchids (Orchidaceae) in Bukit Pasapa Kurrak, Mamasa, West Sulawesi, Indonesia - Hasgun Hasgun; Nurmuliayanti Muis; Muh Rizal Kurniawan Yunus (Center for Ecology, Conservation and Ethnobiology Studies, Universitas Sulawesi Barat, 2025)
Biodiversity refers to the variety of living organisms, encompassing genetic, species, and ecosystem diversity within a particular area. Epiphytic orchids are orchids that grow on other plants but are not parasitic, as they only attach to the trunks, branches, or twigs of living or dead trees without deriving nutrients directly from their hosts. This study aimed to analyze the diversity and distribution patterns of epiphytic orchid species in Bukit Pasapa Kurrak and to explore their implementation as a biological learning resource. This research employed a quantitative approach using an exploratory survey method. Sampling was conducted using a purposive sampling technique. The collected data were analyzed by calculating several ecological indices, including the Important Value Index (IVI), Shannon–Wiener diversity index (H’), Simpson dominance index (C), evenness index (E), and Morisita’s index of dispersion (Id). The results showed that the diversity of epiphytic orchid species in Bukit Pasapa Kurrak was categorized as moderate, with a Shannon–Wiener diversity index of H’ = 1.66. The distribution pattern of epiphytic orchids in the study area was classified as random, with a Morisita index (Ip) of 0.04. Furthermore, validation results from two expert validators indicated that the developed learning resource was highly valid and feasible to implement as a biology learning resource.